DUAL FUNCTIONALITY OF THE ANTI-β1 INTEGRIN ANTIBODY, 12G10, EXEMPLIFIES AGONISTIC SIGNALLING FROM THE LIGAND-BINDING POCKET OF INTEGRIN ADHESION RECEPTORS - Humphries, Jonathan D. (2005)
Although integrins are known to mediate connections between extracellular adhesion molecules and the intracellular actin cytoskeleton, the mechanisms that are responsible for coupling ligand binding to intracellular signalling, for generating diversity in signalling, and for determining the efficacy of integrin signalling in response to ligand engagement are largely unknown. By characterising the class of anti-integrin monoclonal antibodies (mAb) that stimulate integrin activation and ligand binding, we have identified integrin-ligand-mAb complexes that exhibit differential signalling properties. Specifically, addition of 12G10 mAb to cells adhering via integrin α4β1 was found to trigger disruption of the actin cytoskeleton, and prevent cell attachment and spreading, while mAb addition to cells adhering via α5β1 stimulated all of these processes. In contrast soluble ligand binding to either α4β1 or α5β1 was augmented or unaffected by 12G10. The regions of the integrin responsible for differential signalling were then mapped using chimeras. Surprisingly, a chimeric α5 integrin containing the β-propeller domain from the ligand-binding pocket of α4 exhibited the same signalling properties as the full-length α4 integrin, while exchanging or removing cytoplasmic domains had no effect. Thus the mAb 12G10 demonstrates dual functionality, inhibiting cell adhesion and spreading while augmenting soluble ligand binding, via a mechanism that is determined by the extracellular β-propeller domain of the associating α subunit. These findings therefore demonstrate a direct and variable agonistic link between the ligand-binding pocket of integrins and the cell interior that is independent of the α cytoplasmic domains. We propose that either ligand-specific transmembrane conformational changes or ligand-specific differences in the kinetics of transmembrane domain separation underlie integrin agonism.